2015
DOI: 10.1016/j.rbmo.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Habits of cell phone usage and sperm quality – does it warrant attention?

Abstract: Male infertility constitutes 30-40% of all infertility cases. Some studies have shown a continuous decline in semen quality since the beginning of the 20th century. One postulated contributing factor is radio frequency electromagnetic radiation emitted from cell phones. This study investigates an association between characteristics of cell phone usage and semen quality. Questionnaires accessing demographic data and characteristics of cell phone usage were completed by 106 men referred for semen analysis. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…However, we were unable to confirm the finding of previous studies which showed that increased fish intake was related to higher sperm count and sperm morphology (Afeiche et al 2014a). Finally, we did not find any significant association between trouser cell phone use and semen quality which was in line with one previous study (Zhang et al 2016), but different from others (Jurewicz et al 2014a;Zilberlicht et al 2015).…”
Section: Discussionsupporting
confidence: 86%
“…However, we were unable to confirm the finding of previous studies which showed that increased fish intake was related to higher sperm count and sperm morphology (Afeiche et al 2014a). Finally, we did not find any significant association between trouser cell phone use and semen quality which was in line with one previous study (Zhang et al 2016), but different from others (Jurewicz et al 2014a;Zilberlicht et al 2015).…”
Section: Discussionsupporting
confidence: 86%
“…) and mobile phone use (Zilberlicht et al . ). Increased paternal age has also recently been suggested as a risk factor for fertility problems – a pattern that may be set to increase given wider social trends in Western societies relating to later childbearing (Ausmees et al .…”
Section: Introductionmentioning
confidence: 97%
“…The use of mobile telephones is also presented as a risk to their potential fertility and men are advised to change or reduce their use of this technology (Zilberlicht et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations